Ultrahigh conductivity of graphene nanoribbons doped with ordered nitrogen. Issue 11 (2nd October 2019) - Li, Xiao-Fei; Yan, Wei-Wei; Rao, Jia-Rui; Liu, Dong-Xue; Zhang, Xiang-Hua; Cao, Xinrui; Luo, Yi
Abstract : Ordered nitrogen-doping increases carrier density but does not harm the high mobility of GNRs, resulting in ultrahigh conductivities. Abstract : Graphene is an attractive candidate for developing high conductivity materials (HCMs) owing to an extraordinary charge mobility. While graphene itself is a semi-metal with an inherently low carrier density, and methods used for increasing carrier density normally also cause a marked decrease in charge mobility. Here, we report that ordered nitrogen doping can induce a pronounced increase in carrier density but does not harm the high charge mobility of graphene nanoribbons (GNRs), giving rise to an unprecedented ultrahigh conductivity in the system. Our first-principles calculations for orderly N-doped GNRs (referred to as C5 N-GNRs) show that N-doping causes a significant shift-up of the Fermi level (Δ E F ), resulting in the presence of multiple partially-filled energy bands (PFEDs) that primarily increase the carrier density of system. Notably, the PFEDs are delocalized well with integral and quantized transmissions, suggesting a negligible effect from N-doping on the charge mobility. Moreover, the PFEDs can cross the E F multiple times as the ribbon widens, causing the conductivity to increase monotonically and reach ultrahigh values (>15 G 0 ) in sub-5 nm wide ribbons with either armchair or zigzag edges. Furthermore, a simple linear relationship between the doing concentration and the Δ E F was obtained, which provides a robust means for controlling the conductivity of C5 N-GNRs. Our findings should be useful for understanding the effect of ordered atomic doping on the conductivity of graphene and may open new avenues for realizing graphene-based HCMs.